Plant Diversity and Conservation Value of Ayer Hitam Forest, Selangor, Peninsular Malaysia - Ibrahim, Faridah Hanum (Universiti Putra Malaysia Press, 1999)
The Ayer Hitam Forest, a logged-over lowland mixed-dipterocarp forest in the State of Selangor covers an area of 1248 hectares. It is one of the remaining forests left in the Klang Valley besides the Bukit Nenas Forest in Kuala Lumpur. This forest has been leased to Universiti Putra Malaysia(UPM) in 1996 for 80 years for the purpose of education, research and extension. Since then various efforts have been taken to know the biodiversity it houses. Thus, a database on the plants of Ayer Hitam Forest was started in 1998. Several plots have been established and plant collections were made to achieve this and is still progressing. Results presented here are still preliminary. A total of 430 species of seed plants in 203 genera and 72 families occur here. 33 species offerns and fern-allies, 127 timber species, 29 fruit tree species and 98 species with medicinal values were recorded from this forest. Of these taxa, 20 species which are endemic to Peninsular Malaysia are found here, five being new records for Selangor. Although Ayer Hitam Forest is still regenerating, it is nevertheless a rich fragmented ecosytem that needs to be conseroed for future generations to come.